Experimental Analysis Of Stability And Thermal Conductivity For Silica Nanofluid In Water Block Heat Sink - Zulkeflee, Rahmah (Universiti Sains Malaysia, 2019)
Thermal performance has become one of the main issues in electronic industries in line with prevailing development. Conventional working fluid often used by electronic devices has some shortcomings on the efficiency of transferring heat for cooling purposes. Hence, nanofluid is used as replacement is a promising alternative as it will be able to help improvising and more competent than subsist working fluid. In this experiment silica-water based nanofluid with Gum Arabic as surfactant is used. The main purpose of this study is to investigate the effect of different volume concentration of nanoparticles in working fluid of cooling water block on thermophysical properties and stability. Various volume concentration of SiO2 nanoparticles (0.1, 0.3, 0.5) % is used through two step method for dispersion process and nanofluid was dispersed using sonication process for 20 minutes. Temperature distribution on heat sink water block with range of flow rates (0.05 to 0.1) m3/hr and heating power of (20-60) W will be used to determine the efficiency of nanofluid as heat transfer fluids. The effect of different volume concentrations on base temperature of heat sink was found to be decreased up to 7.7%, increment of convective HTC by 4.3% and highest thermal reduction of 26.6% for volume concentrations of 0.3% SiO2 compared to distilled water as conventional fluid. Silica nanofluid shows most stable in GA with ratio of 1:5 surfactant and silica nanoparticles to the extends of 30 days without sedimentation for 0.1% volume concentration. Therefore, silica nanofluid possessed better thermophysical properties than conventional fluid (distilled water) and had the ability to work as thermal fluid in heat transfer system.